Strategy to Increase Sales Through Brand Awareness on Local Brand Instant Coffee Products - Martono, Sri; Prameswari, Dita (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2021)
Background: The strategy to increase sales plays an important role in the sustainability of a company because with the sale the company will get a profit. A company that is able to increase sales will exist in business competition. Currently, not many consumers are aware of the Lokalate brand of instant coffee. Therefore, Lokalate must be introduced to the wider community and build public brand awareness of Lokalate instant coffee products. With brand awareness, it is hoped that it can increase sales of Lokalate brand instant coffee products. Purpose: This study aims to analyze the effect of brand awareness on increasing sales (Study on Local Consumers at An Nuur University). The influence of brand awareness will be analyzed partially and simultaneously on increasing sales. Methods: This type of research uses quantitative research. The population in this study were all students of An Nuur Purwodadi University with a sample of 100 with certain criteria. The sampling technique used purposive sampling technique. Collecting data using a questionnaire that was processed using the SPSS application. Conclusion: The results of the study indicate that the brand awareness variable (X) has a significant effect on increasing sales (Y) so that H1 is accepted. Thus, it can be concluded that product awareness can increase sales increase. Because when consumers are aware of the quality of the product, they will tend to make repeat purchases which can increase the level of sales at the company. Suggestion: For future research agendas, it should be developed in a wider scope in order to produce broader findings and there are gaps with other research as the basis for future research. Keywords: Purchase Decision, Promotion, Price, Consumer